Understanding research - Neuman, William Lawrence , 1950- (Pearson/Prentice Hall, 2012)
Understanding Research is an accessible and visually-appealing introduction to research. Whether students become producers or consumers of research, this text shows them that the subject is both interesting and highly relevant for their lives and professional work